IMPLEMENTATION OF TRAINING AND HUMAN RESOURCES DEVELOPMENT BASED ON POLITEKNIK NEGERI MEDAN WORK CULTURE - Muhammad Alfahmi (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2022)
This study aims to describe the implementation of training and development of human resources based on the work culture of the Politeknik Negeri Medan. For the world of higher education itself, training and human resource development are considered very important, because they have human resources who can meet the operational needs of banks and have a high sense of responsibility for the quality of graduates produced in order to create and fill jobs in the future. The type of research in this research is qualitative with descriptive method. Training and development as well as facilities are factors that can improve employee performance. Especially for the Medan State Polytechnic, the facility factor has a more dominant influence. Therefore, it is recommended that the leadership of the Medan State Polytechnic, in addition to conducting training and development, should emphasize increasing the facilities needed by employees. This can be done by prioritizing the procurement program for facilities that can improve employee performance, such as administrative equipment and transportation facilities.